Precooling scheduling in building ACMV operation - Lin, SanChuan (2015)
Energy efficiency of ACMV systems has gained intense awareness of engineers as a role to relieve the impact of energy production’sby-product to global climate change. One of the solutions to enhance the efficiency is through active control by responding to the capricious factors that affect indoor air temperature, in other words, air-conditioning systemsdo not necessarily operate at constant air flow and cooling rateto maintain the temperature. Such factors, for instance, include the flux of human presence in the room, ambient humidity and outdoor temperatures. However, appertain to ACMVefficiency works usually involve engineers from a diversified field, whereby mechanical engineers possess expertise in ACMV system, building experts possess knowledge of thermal insulation of walls and computer-aid energy simulations, and control engineers play a crucial part in designing the controller that maximise the efficiency of ACMV system ina building. The lack of interaction between engineershinders the facilitation of development of control methodology. In this project, it presents a model of air-conditioned building which is created base on the knowledge of ACMV system and ASHRAE Standards of Building Material and Envelops. The model is to be simulated in EnergyPlus to attain as much control variables and actuators of both building components and ACMV system as possible. Upon completion of the model, an engineering tool, MATLAB is interfaced with EnergyPlus to performpossible extension of the project.The data exchange between the tools facilitatesthe validation of the model, as the comparison between the predicted and simulated results testify thecompliance of performance of ACMV plants with typicalmathematical models. Identification of thermal dynamic system ensues, which is crucial for Model-Based Predictive control, andsimple ARX modelsof three inputs and one output for thermal zones are developed. Given the fact that thermal dynamic system is tremendously complex and the inevitable occurrence of chain effects of controlling oneair damper onthe entire air supplyingand returningnetwork, this model aids the engineers in the researchingand developing of holistic control of ACMV system.